2017
DOI: 10.1186/s40405-017-0026-3
|View full text |Cite
|
Sign up to set email alerts
|

How gambling harms experienced by Pacific people in New Zealand amplify when they are culture-related

Abstract: Pacific people in New Zealand are a minority ethnic population identified in national prevalence studies as having the highest risk of developing gambling problems. As earlier studies identified some links between culture and gambling for this population, our study aimed to deepen understanding of these links and their role in explaining the disproportionate gambling harms experienced by Pacific people. To achieve this aim we employed intersectionality as a theoretical framework to explore the culture-gambling… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
18
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(19 citation statements)
references
References 41 publications
1
18
0
Order By: Relevance
“…Twelve studies include data on culture and five of these discuss Australia and New Zealand [ 48 , 71 74 ]. The included studies largely focus on single groups or comparing indigenous people and migrants to a society, so there are significant gaps that future studies may address.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Twelve studies include data on culture and five of these discuss Australia and New Zealand [ 48 , 71 74 ]. The included studies largely focus on single groups or comparing indigenous people and migrants to a society, so there are significant gaps that future studies may address.…”
Section: Resultsmentioning
confidence: 99%
“…Kolandai-Matchett et al [ 74 ] found that Pacific New Zealand people experienced similar gambling harms to other populations. However, the context of collectivist cultural values meant that additional harm dimensions were present, such as a loss of belonging or isolation, shame, loss of the community’s respect, disruption of trusting relationships, transference of communal responsibilities, and an overall loss of social cohesion.…”
Section: Resultsmentioning
confidence: 99%
“…For example, Hagen et al (2013) discussed the role in which aboriginal women’s experiences of trauma contributed to their experiences of gambling harm, citing an “irresistible pull” towards gambling as a way to escape and cope with problems (p. 366) [63]. Similarly, Māori and Pacific women in New Zealand have been found to disproportionately experience harm from gambling, compared with European women [66, 67]. Research from Morrison (2014) suggests that Māori women experience significant negative effects from EGM gambling; however, these women often only describe the positives of gambling, such as the increased social connections that are not often available to Māori women [66].…”
Section: Introductionmentioning
confidence: 99%
“…Kolandai-Matchett et al (2017) found that Pacific New Zealand people experienced gambling through collectivist cultural values, meaning that additional harm dimensions were present. Some of the listed cultural harms include a loss of belonging or isolation, shame; loss of the community’s respect; disruption of trusting relationships; transference of communal responsibilities; and an overall loss of social cohesion.…”
Section: Resultsmentioning
confidence: 99%